Simultaneous multislice excitation by parallel transmission. Issue 4 (28th May 2013) - Poser, Benedikt A.; Anderson, Robert James; Guérin, Bastien; Setsompop, Kawin; Deng, Weiran; Mareyam, Azma; Serano, Peter; Wald, Lawrence L.; Stenger, V. Andrew
<x xml:space="preserve">Abstract</x> Purpose A technique is described for simultaneous multislice (SMS) excitation using radiofrequency (RF) parallel transmission (pTX). Methods Spatially distinct slices are simultaneously excited by applying different RF frequencies on groups of elements of a multichannel transmit array. The localized transmit sensitivities of the coil geometry are thereby exploited to reduce RF power. The method is capable of achieving SMS‐excitation using single‐slice RF pulses, or multiband pulses. SMS‐pTX is demonstrated using eight‐channel parallel RF transmission on a dual‐ring pTX coil at 3 T. The effect on B1+ homogeneity and specific absorption rate (SAR) is evaluated experimentally and by simulations. Slice‐GRAPPA reconstruction was used for separation of the collapsed slice signals. Results Phantom and in vivo brain data acquired with fast low‐angle shot (FLASH) and blipped‐controlled aliasing results in higher acceleration (CAIPIRINHA) echo‐planar imaging are presented at SMS excitation factors of two, four, and six. We also show that with our pTX coil design, slice placement, and binary division of transmitters, SMS‐pTX excitations can achieve the same mean flip angles excitations at ∼30% lower RF power than a conventional SMS approach with multiband RF pulses. Conclusion The proposed SMS‐pTX allows SMS excitations at reduced RF power by exploiting the local B1+ sensitivities of suitable multielement pTX arrays. Magn Reson Med 71:1416–1427, 2014. © 2013 Wiley Periodicals, Inc.